Jamie Sullivan and Landon Carter : the Unique Characters in Nicholas Sparks’s Novel A Walk To Remember - Felicia Bernadeth Simanjuntak; Syahron Lubis; Ridwan Hanafiah (Journal of Language, Literature and Teaching, 2019)
Abstract This reearch told about main characters in a love  story novel A Walk to Remember between Jamie Sullivan and Landon Carter, when they were seventeen years old, which ended marriage on young ages. The problem was formulated on what were the unique characters of Jamie Sullivan and Landon Carter and how they as characters could develop in that novel. The writer used the qualitative descriptive method and intrinsic approach. . To collect data, the writer followed these steps: (a) reading the whole novel, (b) selecting the physical appearance and attitude of Jamie Sullivan and Landon Carter, (c) classifying the data dealing with the problem of the research (d) summarizing. The results showed they were uniqueness characters because Jamie's uniqueness were she married at young age when she was dying of leukemia, she always carried the Bible and read it, her appearances, and her way to socialize with others; Landon's uniqueness were he wanted to help although he was a rebel boy, he changed be the good man because his love for Jamie, and he let his life the way of the Bible taught as the example he still married Jamie although he knew that Jamie was dying. Sparks as the author of novel portrayed them very clearly such as their age, family background, location they live, physical appearance, personality, and conflict within the story Keywords: literature, novel, the elements of novel, character